AN ANALYSIS OF STUDENT READING INTEREST IN SCIENTIFIC ARTICLE - Faikatul Jannah; Mamluatun Ni’mah; Shofiatul Hasanah (Journey: Journal of English Language and Pedagogy, 2023)
The purpose of this study was to find alternative strategies to increase student interest in reading, especially tadris English students at Zainul hasan Islamic University with several aspects, the role of teachers in teaching reading skills, activities to increase reading interest, media interest in reading and efforts to increase reading interest. This research uses qualitative descriptive method. Consisting of this research are lecturers and students. Data were obtained through observation and documentation interviews. The result of this research is that lecturers know their role as an effort to increase reading interest. Lecturers also use sheet-shaped article media to support the learning process. Based on this research. based on the results of the study concluded that efforts to increase interest in reading at the University of Islam Zainul Hasan has increased.